Crystalline Properties of Cassava (Manihot esculenta Crantz) Starch and Its Associated Biofoam - Philipus J Patty; Synodalia C Wattimena (Jurnal Fisika dan Aplikasinya, 2023)
Making foam using starch as an alternative material to replace a conventional material, polystyrene, is one of the solutions to solve an environmental problem due to the waste of foam made from polystyrene cannot be degraded. This study aims to analyze the crystalline properties of cassava starch and biofoam made from it using X-ray diffraction (XRD) spectroscopy. From the XRD data of cassava starch, the peaks of 2θ were analyzed to determine the type of cassava starch used in this study. The index of crystallinity of both cassava starch and its associated biofoam was calculated from XRD data. XRD data of cassava starch show 4 main peaks of 2θ: 15.0◦ , 17.0◦ , 17.9◦ , and 23.0◦ , and 3 minor peaks at 11.0◦ , 20.0◦ , 26.0◦ . Based on the main peaks from this XRD data, cassava starch can be categorized as an A-type starch. For cassava starch biofoam, there is only 1 main peak of 2θ at 19.7◦ , and 5 minor peaks at 11.0◦ , 15.4◦ , 21.7◦ , 23.0◦ , and 26.4◦ . The decrease in the crystallinity from the starch to the associated biofoam is shown by the decrease in the index of crystallinity, which decreases from 41.0% in starch to 28.3% in biofoam.